2023
DOI: 10.3847/1538-4357/acf712
|View full text |Cite
|
Sign up to set email alerts
|

JWST's TEMPLATES for Star Formation: The First Resolved Gas-phase Metallicity Maps of Dust-obscured Star-forming Galaxies at z ∼ 4

Jack E. Birkin,
Taylor A. Hutchison,
Brian Welch
et al.

Abstract: We present the first spatially resolved maps of gas-phase metallicity for two dust-obscured star-forming galaxies at z ∼ 4, from the JWST TEMPLATES Early Release Science program, derived from NIRSpec integral field unit spectroscopy of the Hα and [N ii] emission lines. Empirical optical line calibrations are used to determine that the sources are globally enriched to near-solar levels. While one source shows elevated [N ii]/Hα ratios and broad Hα emission consistent with the presence of an active galactic nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…Our MBB-based median values are also consistent with the estimates of the ALESS and AS2UDS SMGs when the restframe 870 μm luminosity is used as a tracer of M dust (Birkin et al 2021). The relatively low gas-to-dust ratio could suggest supersolar gas-phase metallicity, which is in line with SMGs being heavily dust-enriched and consistent with some recent results (Birkin et al 2023;Eales et al 2023;Peng et al 2023).…”
Section: Gas-to-dust Mass Ratiosupporting
confidence: 91%
“…Our MBB-based median values are also consistent with the estimates of the ALESS and AS2UDS SMGs when the restframe 870 μm luminosity is used as a tracer of M dust (Birkin et al 2021). The relatively low gas-to-dust ratio could suggest supersolar gas-phase metallicity, which is in line with SMGs being heavily dust-enriched and consistent with some recent results (Birkin et al 2023;Eales et al 2023;Peng et al 2023).…”
Section: Gas-to-dust Mass Ratiosupporting
confidence: 91%
“…Originally discovered as a submillimeter source by the South Pole Telescope (SPT; Vieira et al 2013), SPT0418−47 is known to have a high SFR (∼280 M e yr −1 ) with a dense, solarmetallicity interstellar medium, from observations with the Atacama Pathfinder EXperiment and ALMA (De Breuck et al 2019) and from JWST spectroscopy (Birkin et al 2023). Spilker et al (2020) also observed an outflow of molecular gas in this galaxy with M 150 out  ~Me yr −1 .…”
Section: Introductionmentioning
confidence: 92%
“…For both codes, we use a flexible attenuation curve parameterization that allows for a variable UV-optical slope and V-band attenuation: specifically, CIGALE uses the parameterization from Boquien et al (2019) and PROSPECTOR that of Kriek & Conroy (2013). The metallicity is allowed to vary for SPT0418A, and we apply a uniform prior on the metallicity between 80% and 125% of solar, consistent with De Breuck et al (2019; 0.3 < Z/Z e < 1.3), and based on our teamʼs spectroscopic analysis (Birkin et al 2023).…”
Section: Stellar Mass Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed this algorithm in the TEMPLATES ERS collaboration to replace the outlier rejection step for the reasons outlined above (e.g., Birkin et al 2023). We continue to use this algorithm in tandem with the current outlier rejection step in the pipeline to achieve the cleanest data products possible (see Section 3 for the motivation for this combined choice, for jwst pipeline versions 1.11.3 and later).…”
Section: The Algorithmmentioning
confidence: 99%